2018
DOI: 10.1093/rb/rby011
|View full text |Cite
|
Sign up to set email alerts
|

Application of osteoinductive calcium phosphate ceramics in children’s endoscopic neurosurgery: report of five cases

Abstract: This work aimed at investigating the possibility and effectiveness of osteoinductive calcium phosphate (CaP) ceramics to close the drilled skull holes and prevent the postoperative cerebrospinal fluid (CSF) leaking in children’s endoscopic neurosurgery. Five children patients (four boys and one girl, 3- to 8-years old) underwent the surgery, in which the endoscopic third ventriculostomy (ETV) was operated in four cases of hydrocephalus, and biopsy and ETV were both performed in one case of pineal tumor. The dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The osteoconductive properties of these bone substitutes are widely recognized, but the most frequent criticism of these materials is that they only have osteoconductive properties, but not osteoinductive properties [8]. In contrast with these data, a few recent reports highlighted the osteoinductive properties of a calcium-phosphate complex (also found in bone substitutes) based on several pathways, as stimulation of mesenchymal stem cells recruitment and commitment through an osteoblastic lineage, together with a strong angiogenic process [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The osteoconductive properties of these bone substitutes are widely recognized, but the most frequent criticism of these materials is that they only have osteoconductive properties, but not osteoinductive properties [8]. In contrast with these data, a few recent reports highlighted the osteoinductive properties of a calcium-phosphate complex (also found in bone substitutes) based on several pathways, as stimulation of mesenchymal stem cells recruitment and commitment through an osteoblastic lineage, together with a strong angiogenic process [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The orthopedic application of CaP bioceramics in bone repair was carried out in the approximately 1980s. , Previous studies have confirmed that CaP bioceramics can be used in fresh tooth sockets for bone regeneration and spinal fusion and as a bone void filler in a variety of bone fractures. ,, It is well-accepted that the porous structure is crucial for osteoinductive performance of bioceramics and subsequent bone regeneration. ,, Our group was the first few research groups who introduced the H 2 O 2 foaming method to prepare porous CaP bioceramics in 1998 and confirmed that this strategy can induce the formation of abundant interconnected open pores with a variety of sizes. , This porous structure later was proven to be beneficial in blood vessel formation and excellent osteogenic capacity. ,, In 2019, we demonstrated that porous CaP bioceramics prepared by the gas-forming method can be clinically used during children’s endoscopic neurosurgery so as to prevent postoperative cerebrospinal fluid leakage in endoscopic neurosurgery of young patients . Although the preparation and use of multiphase CaP bioceramics have been extensively reported previously, as far as we know, no study has designed a porous CaP bioceramic with a spherical core–shell structure for bone repair.…”
Section: Discussionmentioning
confidence: 99%
“…28,48,59 In 2019, we demonstrated that porous CaP bioceramics prepared by the gas-forming method can be clinically used during children's endoscopic neurosurgery so as to prevent postoperative cerebrospinal fluid leakage in endoscopic neurosurgery of young patients. 60 Although the preparation and use of multiphase CaP bioceramics have been extensively reported previously, as far as we know, no study has designed a porous CaP bioceramic with a spherical core−shell structure for bone repair. In this study, we fabricated two different porous core−shell bioceramic granules, BCP@HA and HA@BCP, and assessed their in vitro and in vivo bone regenerating ability.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most promising functional biomaterials, calcium phosphate (CaP) ceramics, including hydroxyapatite (HA), β-tricalcium phosphate (β-TCP) and their compounds, have been widely investigated and successfully used for clinical application because of similar inorganic components with natural bone. CaP ceramics have been found with excellent biocompatibility, osteoconductivity and osteoinductivity, which is influenced by many material factors [ 21 , 22 ]. Generally, the properly interconnected porous structure and surface micro- and nano-topography provide CaP ceramics with superior osteoinductivity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The highly porous scaffolds allow mass transport, cell adhesion and bone ingrowth, without adding any exogenous cell and growth factors [ 20 ]. In practice, its effcacy in guiding bone regeneration was confirmed not only by the segmental bone defect in animal models but also by the calvarial defects in children [ 22 , 24 ]. Therefore, CaP ceramics may have the potential to enhance bone formation on the sacrum following nerve-sparing surgery.…”
Section: Introductionmentioning
confidence: 99%